How to Support Vulnerable Citizens during the COVID-19 Lockdown: A Community Initiative from Ubiquitous Network Perspectives - Hiroko Oe; Max Weeks (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
The current COVID-19 lockdown situation has had a negative impact on people’s connectedness which also has an influence on the well-being of the citizens (Canady, 2020; Hare-Duke, 2019; Oe, 2020). The enhancement of human interaction and networking is a key topic to sustain people’s health, and this has been on the emergent agenda during the current COVID-19 situation (Oe, 2020).To tackle this issue, one theory that could be employed is the efficacy of community members’ engagement, as proposed by McMillian and Chavis (1986), who summarised a key ‘sense of community’ model. This model suggests four main dimensions should be strengthened to engage community members in supporting vulnerable people: a sense of belonging, an emotional connection, fulfilment of needs, and influence (Bermea et al., 2019).This conceptual paper aims to enhance the discussion of how best to support vulnerable isolated citizens during the COVID-19 lockdown situation. A proposition framework suggests actionable implications with tangible recommendations for the relevant stakeholders. The authors propose two key themes to be considered: (1) how to meet needs and provide support in the virtual network community, and (2) how to implement assistive technologies as a ubiquitous network paradigm as a community safety net for all.